Evidence for the sinistral Porcupine shear zone in North Yukon (Canadian Arctic) and geotectonic implications - von Gosen, Werner; Piepjohn, K.; Mcclelland, W. C.; Colpron, M. (Special Paper of the Geological Society of America, 2019)
Structural analysis of Neoproterozoic to lower Paleozoic rocks near Old Crow, in North Yukon, show that they were affected by widespread, but distributed sinistral shear zone deformation. This tectonic event occurred under brittle-ductile conditions, in the early Paleozoic, prior to intrusion of Late Devonian granitoids of the Old Crow plutonic suite (368-375 Ma). Although outcrops are scattered, the shear zone deformation can be inferred to extend over a broad similar to W-E corridor, similar to 10-20 km-wide and similar to 145 km long, from eastern Alaska into northern Yukon. The sinistral Porcupine shear zone is interpreted to represent a major, early Paleozoic crustal structure along which elements of NE Laurentian and Caledonian affinities in the Arctic Alaska terrane were transferred across the Arctic region during the Paleozoic. Our observations do not support major Paleogene dextral strike-slip deformation along the Porcupine River near Old Crow.
CRIS-Team WoS Importer:2019-11-15